Tumpang Tindih Kewenangan Pengembangan Kawasan Ekonomi Khusus Batam - Alexander Yanuard Dalla; Friska Natalia Hutabarat (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
The enactment of regional autonomy in Batam City created a dualism of authority between the Batam City Government (Batam City Government) and Batam Business Entity (BP Batam). The issue of dualism of authority resulted in disharmony between the two institutions in the administration of government in Batam City. Government efforts have also not been able to resolve this issue. One of the strategies pursued is to make Batam a Special Economic Zone (SEZ). In this regard, this study aims to identify the overlapping of authority between the Batam City Government and Batam Concession Agency; and find the impact of overlapping authority on the development of Special Economic Zones. This study is a policy research, using a descriptive method with a qualitative approach, namely explaining the events of overlapping authority that occurred in the administration of government and its impact on the development of Special Economic Zones in Batam. Data collection is done through desk research (documentation techniques) and field studies, namely in-depth interviews (in-depth interviews) and Focused Group Discussion (FGD). The results of the study show that overlapping authority occurred in several aspects of government related to Licensing, Land, Spatial Planning, Forests, and Assets. This overlapping of authority impedes the development of Special Economic Zones, namely the issue of division of work areas, assets and types of permits. The solutions offered are the need for the division of authority based on the division of work areas or zoning so that it becomes clear the work space of BP Batam and Pemko Batam.